A review of traditional and emerging methods to characterize lipid–protein interactions in biological membranes. Issue 17 (7th September 2015) - Hsia, Chih-Yun; Richards, Mark J.; Daniel, Susan
<x xml:space="preserve">Abstract</x> Lipid–protein interactions are essential for modulating membrane protein structures and biological functions in the cell plasma membrane. In this review we describe the salient features of classical and emerging methodologies for studying protein–lipid interactions and their limitations.